Digital assets from an Islamic jurisprudential perspective - Md Tahir, Siti Nurhidayah; Md. Sawari, Mohd. Fuad; Zakaria, Mohamad Sabri (Faculty of Economics, Accountancy and Management, Universiti Islam Selangor, 2025)
The study aims to define digital assets from an Islamic jurisprudential perspective by establishing a comprehensive conceptual framework rooted in classical Islamic legal principles. Against the background of rapid technological advancement and the emergence of various digital value representations (from cryptocurrencies to non-fungible tokens), this research addresses the knowledge gap in understanding these novel assets through Islamic jurisprudential perspective. Employing qualitative content analysis, the study examines diverse source materials including classical Islamic jurisprudential texts, contemporary scholarly literature, and regulatory frameworks, while conducting etymological analysis of relevant Arabic terminology. Findings reveal that digital assets can be defined as intangible, electronically stored resources that hold economic value and are accessible through digital platforms, with their Islamic jurisprudential valuation determined by four primary factors: their classification as wealth (māl), societal acceptance (ʿurf), compliance with Islamic principles, and ownership status. The research concludes that while digital assets represent modern financial and technological innovations, they retain essential attributes that align with traditional Islamic asset classifications, allowing them to be effectively evaluated through established Islamic jurisprudential frameworks when adapted to contemporary contexts.